1992
DOI: 10.1182/blood.v80.3.795.bloodjournal803795
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and analysis of in vivo expression of murine P- selectin

Abstract: P-selectin (CD62) is a rapidly inducible cell surface adhesion molecule that is expressed on platelets and endothelial cells and mediates their interaction with leukocytes. In vitro studies have suggested that this receptor may play an important role in hemostasis and in inflammatory response to tissue injury. We report the molecular cloning and sequencing of murine cDNA for P-selectin. The lectin, epidermal growth factor (EGF)-like, transmembrane, and cytoplasmic domains are highly conserved between mouse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Residues in bold are numbered according to their positions in the human sequence. The entire sequence is highly conserved, and residues Ser772 through to Ala784 (underlined) are invariant, in human [34], porcine [35], bovine [36], murine [37], rat [38], canine and ovine sequences. The canine sequence has the GenBank™ accession number M88170 (Manning AM, Sanders WE Jr, Kukielka GL, Dore M, Rosenbloom CL, Hawkins HL, Michael LH, Entman ML, Smith CW, Beaudet AL, Anderson DC.…”
mentioning
confidence: 99%
“…Residues in bold are numbered according to their positions in the human sequence. The entire sequence is highly conserved, and residues Ser772 through to Ala784 (underlined) are invariant, in human [34], porcine [35], bovine [36], murine [37], rat [38], canine and ovine sequences. The canine sequence has the GenBank™ accession number M88170 (Manning AM, Sanders WE Jr, Kukielka GL, Dore M, Rosenbloom CL, Hawkins HL, Michael LH, Entman ML, Smith CW, Beaudet AL, Anderson DC.…”
mentioning
confidence: 99%
“…Up‐regulation of endothelial P‐selectin in vivo has been demonstrated following complement‐induced injury [23]. Recent animal studies have suggested that P‐selectin expression can be induced by cytokines including IL‐1 and tumour necrosis factor (TNF) [24, 25]. This may represent one mechanism by which endogenous GC could regulate P‐selectin expression, given that ADX has been previously shown to increase IL‐1 release in in vivo and in vitro studies [26, 27] and to influence the response to IL‐1 and TNF [28].…”
Section: Discussionmentioning
confidence: 99%
“…A certain number of amino acids are conserved, in a region spanning residues 359-457, in human and rat, but not in mouse P-selectin ( Figure 3). In that context it is of interest to note that mouse P-selectin is highly homologous, with the exception of SCR 2 [23], to its human counterpart. Homologue replacement mutagenesis of 10 conserved amino acids, spanning residues 359-457 was performed to locate those implicated in the LYP20 epitope.…”
Section: Homologue Replacement Mutagenesis Of the Region Spanning Resmentioning
confidence: 99%